2011
DOI: 10.1016/j.applthermaleng.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study and numerical simulation of a ground source heat pump plant, applied to a residential building

Abstract: To evaluate the efficiency of ground source heat pump (GSHP), an application is studied in a residential building divided in two independent apartments blocks. The numerical results are produced by using the software tool TRNSYS 16. The results include the trends of the thermo-climatic variables and a comparison between conventional and geothermal systems analyzing operational and capital costs. The GSHP studied in this paper produces a thermal power output of 29 kW in winter and a cooling power output of 26 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Desideri et al [10] showed that the operating costs necessary to heat the building with the GSHP, are lower than the ones for heating the building with a natural gas boiler. Previous studies are mainly focused on the use of horizontal water ground heat exchangers [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Desideri et al [10] showed that the operating costs necessary to heat the building with the GSHP, are lower than the ones for heating the building with a natural gas boiler. Previous studies are mainly focused on the use of horizontal water ground heat exchangers [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Heat pumps are one option among available energy efficient equipment [2,9,10] and their combination with solar thermal energy is promising. Solar thermal assisted heat pump systems (SAHPS) are usually powered by electricity and indirectly by fossil fuel.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the articles [4][5][6][7] outline economic analysis of HP systems; however, their investment costs are not evaluated. The authors of [8][9] propose numerical simulation and economic modelling of HP for residential heating systems. Economic and energy analysis is presented in [10] where investment costs are evaluated.…”
Section: Introductionmentioning
confidence: 99%